A Stop by Muthakkarat al-Bahhar (Sea Memoirs) - Shaker Amery (دراسات في اللغة العربيّة وآدابها)
Â Â  The sea was the principal means of subsistence for people in Kwait in the past. It provided them both pearls and fish, people also used it as a route to export and import goods. It was very difficult to work in the sea and sailors often lost their lives there. The first part of this article concerns one of the longest Kwaiti poems written by the contemporary Kwaiti poet, Muhammad al-Fayez, who travelled along with sailors and returned home to find his family in dire misery. The second part of the article is a critical analysis of the poem asserting these features about the poem: Â  Â· This poem is the first attempt at recording Kwaiti marine history by a poet who was himself a seafarer. Â  Â· We can notice obvious traces of asSayyab and alBayati in the Muthakkarat al-Bahhar. Â  Â· Al-Fayez successfully painted a vivid picture of divers and voyages. Â  Â· Universal human feelings are expressed in specific experiences with the poet directly involved in them. Â Â Â